Diversity in New Zealand early childhood education: challenges and opportunities. Issue 2 (2nd April 2016) - Shuker, Mary Jane; Cherrington, Sue
ABSTRACT: The early childhood education (ECE) sector in New Zealand has long been recognised for the diversity of service types and range of organisations involved in delivering ECE. However, less attention has been paid to diversity within individual ECE services. This article draws on a national survey carried out as part of a larger project, The Diversity of Diversity in Early Childhood Education, focusing on teachers' perceptions of challenges and successes encountered when working with children from diverse family backgrounds. Educators' attitudes towards diversity clearly influence whether they perceive working with diverse children and families positively or as a challenge. We argue that possessing positive dispositions and attitudes that enable educators to truly welcome, acknowledge and embrace diversity, together with access to professional knowledge and support services, are critical. The implications of this for policy and practice are then considered.